Improving the Eighth Grade Students’ Reading Comprehension of Recount Texts through DRAW Strategy at SMP Negeri 28 Palembang: A Classroom Action Research - Aminah Nurhasanah (Jurnal Bahasa dan Sastra, 2020)
Abstract: This article reports the results of an action research which involved eighth grade students of SMP Negeri 28 Palembang. The objective of the research was to improve students’ reading comprehension on recount texts by means of DRAW (Draw, Read, Attend, Write) strategy. The study was conducted due to several underlying problems, namely: (1) the students experienced difficulties in understanding reading texts, (2) the students were afraid or reluctant to read loudly due to the lack of pronunciation skills, (3) the students reading’s comprehension needed to be improved, i.e. by improving students’ reading comprehension on recount texts, (4) the students did not understand the purpose of reading texts, (5) The students were rarely taught by using effective strategies. This research was conducted in two cycles, each cycle consisted of four steps, namely: (1) plan, (2) action, (3) observation, and (4) reflection. Findings show that there was increasing average score from cycle 1 (64.22) to cycle 2 (75.63). It means that was11, 41% improving reading ability to cycle 2. Based on the results, it is concluded that DRAW strategy can improve students’ reading comprehension on recount texts through two cycles of the implementation of DRAW strategy. Keywords: recount text, DRAW strategy Abstrak: Artikel ini melaporkan hasil penelitian tindakan kelas yang melibatkan   kelas VIII (delapan) di SMP Negeri 28 Palembang. Tujuan dari penelitian tindakan kelas ini adalah untuk memperbaiki pemahaman siswa membaca recount text dengan menggunakan strategi DRAW( menggambar, membaca, mengikuti dan menulis). Studi ini diadakan untuk memperbaiki pemahaman siswa membaca. Adapun permasalahan dari studi ini adalah: (1)Siswa mengalami kesulitan dalam  memahami text membaca. (2) Siswa takut dan ragu ketika diminta membaca nyaring karena masih lemah dalam melafalkan kata. (3) Pemahaman siswa membaca perlu diperbaiki, misalnya dengan memperbaiki pemahaman siswa membaca recount text. (4) Siswa tidak mengetahui tujuan dari text. (5) Siswa jarang diajarkan dengan menggunakan strategi belajar yang efektif.   Penelitian tindakan kelas ini dilaksanakan dengan menggunakan dua siklus, masing-masing setiap siklus ada 4 (empat) tahap, yaitu : (1) rencana, (2) tindakan, (3) observasi, (4) refleksi. Hasil temuan menunjukkan ada peningkatan nilai rata-rata dari siklus ke satu (64.22) ke siklus ke dua (75.63). Ini berarti bahwa ada peningkatan kemampuan membaca pada siklus ke dua. Berdasarkan hasil ini, dapat disimpulkan bahwa strategi DRAW dapat memperbaiki pemahaman siswa membaca recount text melalui 2(dua) siklus penerapan strategi DRAW. Kata-kata kunci: recount text, strategi DRAW